Takagi–Sugeno Fuzzy System to Predict Discharge Ignition Probability in the Foreline Pressure Range; Key Engineering Materials; Vol. 683 : Multifunctional Materials: Development and Application - Hodashinsky I.; Medovnik A.; Sarin K.; Zykov D. D. Dmitry Dmitrievich; Volkov V. G. Vladimir Grigorievich (Elaboration and Simulation of Processes in Materials Science, 2016)
Title screen